CAR-CIK vs. CAR-T: benchmarking novel cytokine-induced killer cells as solid tumor immunotherapy in ErbB2+ rhabdomyosarcoma - Moser, Laura M.; Heim, Catrin; Koschade, Sebastian E.; Wendel, Philipp; Bozkurt, Süleyman; Harenkamp, Sabine; Kreyenberg, Hermann; Merker, Michael; Münch, Christian; Gradhand, Elise; Vogler, Meike; Ullrich, Evelyn; et al. (Frontiers in Immunology, 2025)
IntroductionCAR-T cell therapy, though successful in hematologic malignancies, faces challenges in solid tumors due to limitations of autologous T cells. Cytokine-induced killer (CIK) cells can be given safely across allogeneic barriers and constitute alternative effector cells generated from healthy donors. CIK cells are a heterogenous population of predominantly T cells with a mixed natural killer (NK) phenotype and combine non-MHC-restricted cytotoxicity with potent anti-tumor capacity of the adaptive immune system. Here, we characterize and compare efficacy, phenotypic subpopulations and modes of action of CAR-CIK cells and conventional CAR-T cells from same-donor samples in ErbB2+ rhabdomyosarcoma (RMS).MethodsTo benchmark CAR-CIK against conventional CAR-T cells, effector cells were generated from same-donor samples and lentivirally transduced with a second generation CD28-CD3ζ CAR. Effector subpopulations and their dynamics upon target cell exposure were phenotypically characterized by flow cytometry. Efficacy was assessed in human ErbB2+ RMS cancer cell lines and primary patient samples in vitro and ex vivo using cytotoxicity and spheroid co-incubation assays. Modes of action were assessed by comparing cytokine secretion profiles using bead-based multiplexed flow cytometry and by liquid chromatography mass spectrometry whole cell proteomics. Finally, we used an in vivo model of RMS mimicking minimal metastatic residual disease to compare anti-tumor potency of CAR-CIK vs. CAR-T cells and to assess their target organ infiltration.ResultsIn vitro assays demonstrated superior cytotoxicity of CAR-CIK cells against RMS cell lines and primary tumor samples. Long-term co-incubation with tumor spheroids led to expansion of CAR-CIK cells and enrichment of CD3+CD56+ TNK cells. CAR-CIK cell cytokine signature showed significantly increased secretion of effector molecules like interferon-γ, perforin and granulysin, and lower secretion of Th2 cytokines IL-2, IL-4 and IL-10. Whole cell proteomics showed corresponding upregulation of chemokine signaling and NK-cytotoxicity pathways in CAR-CIK cells. In NSG mice xenografted with ErbB2+ RMS, a single injection of either CAR-effector cells strongly impeded metastatic tumor development and significantly improved survival.ConclusionOur results demonstrate that CAR-CIK cells are at least equipotent to CAR-T cells. Combined with their favorable safety profile and allogeneic applicability, these findings position CAR-CIK cells as promising immune effectors for solid tumors.